(untitled) (قضايا سياسية, 2022)
The papers discussion the issue of regional security for the Arab Gulf states, what are the limits of this security and the countries that fall within the regional sphere of the countries of the Gulf Cooperation Council, and how the premise of regional security was always attracted in a direct way with what these countries possess in terms of internal components on the one side and with the growing strength of states The regional neighborhood on the other side, and from this standpoint, the Gulf Cooperation Council countries were aware of the importance of their components and the extent of the regional threat to them. They are moving on the basis of this realism (to strengthen and build collective security) mainly led by the Kingdom of Saudi Arabia and in cooperation with a group of regional powers to balance the Iranian threat that He remained an obsession that haunted its aspirations, in addition to his regional roles, and made the issue of achieving its collective security an extremely complex issue.